Antioxidants: A Way to Curb Oxidative Stress: The role of antioxidants in maintaining a balanced oxidative state (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Free radicals such as reactive oxygen species (ROS) are produced and quenched during normal cellular metabolism in a balance in human body. The imbalance generates oxidative stress which is associated with weak immune system causing several diseases. Antioxidants play a crucial role in reducing this oxidative stress by terminating the chain reactions of free radicals and reinstating the balance.